Tunable single-photon emission from dipolaritons - Kyriienko, Oleksandr (2017)
We study a system comprising of a double quantum well embedded in a micropillar optical cavity, where strong coupling between a direct exciton, an indirect exciton, and a cavity photon is achieved. We show that the resulting hybrid quasiparticles—dipolaritons—can induce strong photon correlations and lead to antibunched behavior of the cavity output field. The origin of the observed single-photon emission is attributed to unconventional photon blockade. We find that the second-order equal-time correlation function g^(2)(0) can be tuned over a large range by using an electric field applied to the structure, or by changing the frequency of the pump. This allows for on-the-flight control of cavity output properties and is important for the future generation of tunable single-photon-emission sources.